Body Fat and Body-Mass Index among a Multiethnic Sample of College-Age Men and Women. (8th April 2013) - Carpenter, Catherine L.; Yan, Eric; Chen, Steve; Hong, Kurt; Arechiga, Adam; Kim, Woo S.; Deng, Max; Li, Zhaoping; Heber, David
Abstract : Obesity prevalence and average body composition vary by US race and gender. Asian Americans have the lowest prevalence of obesity. Relying on body-mass index (BMI) to estimate obesity prevalence may misclassify subgroups that appear normally weighted but have excess body fat. We evaluated percentage body fat (PBF) and BMI to determine whether BMI reflects PBF consistently across different races. 940 college students were recruited from a local public university over four consecutive years. We measured PBF by bioelectrical impedance analysis (BIA), weight by physicians' scales, and height with stadiometers. Our sample comprised Asians (49%), Caucasians (23%), Hispanics (7%), and Other (21%). Participants averaged 21.4 years old; BMI was 22.9 kg/m 2 ; PBF was 24.8%. BMI and PBF varied significantly by race and gender ( P value = 0.002 and 0.005 for men; 0.0009 and 0.0008 for women). Asian-American women had the lowest BMI (21.5 kg/m 2 ) but the second highest PBF (27.8%). Linear association between BMI and PBF was the weakest (r 2 = 0.09 ) among Asian-American women and BMI had the poorest sensitivity (37%) to detect PBF. The high PBF with low BMI pattern exhibited by Asian-American women suggests that they could escape detection for obesity-related disease if BMI is the sole measure that estimates body composition.